Systemic inflammation as a driver of health disparities among sexually-diverse and gender-diverse individuals. (July 2021) - Diamond, Lisa M.; Dehlin, Adrian J.; Alley, Jenna
Abstract: Sexually-diverse individuals (those who seek sexual or romantic relationships with the same and/or multiple genders) and gender-diverse individuals (those whose gender identity and/or expression differs from their birth-assigned sex/gender) have disproportionately high physical health problems, but the underlying biological causes for these health disparities remain unclear. Building on the minority stress model linking social stigmatization to health outcomes, we argue that systemic inflammation (the body's primary response to both physical and psychological threats, indicated by inflammatory markers such as C-reactive protein and proinflammatory cytokines) is a primary biobehavioral pathway linking sexual and gender stigma to physical health outcomes. Expectations and experiences of social threat (i.e., rejection, shame, and isolation) are widespread and chronic among sexually-diverse and gender-diverse individuals, and social threats are particularly potent drivers of inflammation. We review research suggesting that framing "minority stress" in terms of social safety versus threat, and attending specifically to the inflammatory consequences of these experiences, can advance our understanding of the biobehavioral consequences of sexual and gender stigma and can promote the development of health promoting interventions for this population. Highlights: Sexually-diverse and gender-diverse (SGD) individuals face notable health disparities. SGD individuals face chronic social stigma and marginalization. Social threat (rejection, shame, exclusion) promotes systemic inflammation. Systemic inflammation may be a key driver of SGD health disparities. We need systematic research linking different types of social threat to SGD health.